2023
DOI: 10.1108/ijmf-05-2022-0224
|View full text |Cite
|
Sign up to set email alerts
|

Earnings quality, institutional investors and corporate cash holdings: evidence from India

Abstract: PurposeThis paper aims to examine the relationship between earnings quality and corporate cash holdings in an emerging economy. Existing literature posits that earnings quality is a result of information asymmetry and firms with lower earnings quality increases cash holdings, to shield the firm from future uncertainties. In this paper, the authors propose a ‘private benefits hypothesis’, which suggests that lower earnings quality is an indicator of opportunism and expropriation of resources in the firm, throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 114 publications
1
1
0
Order By: Relevance
“…The findings on firm size are consistent with the European countries listed companies (Alomran, 2023). It supports the pecking order theory, which finds that large-size firms hold more cash.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The findings on firm size are consistent with the European countries listed companies (Alomran, 2023). It supports the pecking order theory, which finds that large-size firms hold more cash.…”
Section: Discussionsupporting
confidence: 86%
“…However, the GCC countries reported that the existence of investment committees and their interaction with institutional ownership were positively associated with cash holdings. Whereas, the European countries reported negative association between institutional shareholding and cash holding (Alomran, 2023). The findings of firm size lend support to the pecking order theory that propagates that large firms with more profitability are likely to hold more cash.…”
Section: Resultsmentioning
confidence: 99%
“…(Chang et al, 2018) indicate that REM has a positive impact on stronger cash-holding values in companies with more financial debt constraints. Empirical analysis by Chada & Varadharajan, (2023)confirms that the firms with higher earnings quality reduce cash. Meanwhile, opposite results were found by (Kumar et al, 2023) who found that REM had a negative effect on accounting performance and market performance.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, it is assumed that the institutional owner in the unit of analysis is the short-term owner so that the level of ownership weakens the issuer's level of earnings quality. Furthermore, institutional investors reduce their shareholding in firms with higher earnings quality, explaining the negative impact of institutional ownership on earnings quality (Chada and Varadharajan, 2023).…”
Section: Institutional Ownership On Earnings Qualitymentioning
confidence: 99%